EMERGING ARCHITECTURES FOR PROCESSOR-IN-MEMORY CHIPS: TAXONOMY AND IMPLEMENTATION - A Lapshinsky Valery (RUDN Journal of Engineering Research, 2016)
The emergence of PIM (processing-in-memory) die and Date-Centric systems (DCS) and near- data processing approach (NDP) has given rise to the need of developing architectural taxonomy for multi-core PNM (processing near memory) hardware with multi-level memory structure. PIM die (in Russian technical literature usually used terms chips or crystals) considered as an effective alternative to conventional SRAM/DRAM/Flash-memory on Cache-CPU/Main Memory/Storage Class Memory and Storage levels. In the past decade, a few different methods to classify and to implement PIM die and DCS/NDP systems proposed. These approaches are either software interfacing with computing, hierarchical and massively parallel SIMD processing approaches etc. In this paper, presented summarized prolegomena for PIM die architecture and implementation. In particular, in form of basic PIM chips and nanostores.